2016
DOI: 10.4070/kcj.2016.46.5.672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbidity among People with Hypertension: The Korea National Health and Nutrition Examination Survey 2007-2013

Abstract: Background and ObjectivesJoint National Committee guidelines attempt to vary treatment recommendations for patients based on considerations of their comorbidities. The aim of the present study is to estimate the age-standardized prevalence of common comorbidities among Korean hypertension patients.Subjects and MethodsWe analyzed the Korea National Health and Nutrition Examination Survey from 2007 to 2013. Among the 58423 participants, 30092 adults, aged ≥30 yrs who completed a health examination and interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 19 publications
6
34
0
8
Order By: Relevance
“…In Brazil, the prevalence of diabetes in a multicenter study was 19.7%; and 50.4% of this was not previously diagnosed and 79.1% presented intermediate hyperglycemia, showing the serious problem of the disease in the country (26) . Regarding the other comorbidities that were identified, the findings were similar to those of the study that showed that hypertensive patients had a higher prevalence of dyslipidemia, chronic kidney disease, obesity, diabetes and cardiovascular diseases, including stroke, acute myocardial infarction and angina (27) . The presence of multimorbidities in hypertensive individuals may contribute to potential complications for increased mortality.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In Brazil, the prevalence of diabetes in a multicenter study was 19.7%; and 50.4% of this was not previously diagnosed and 79.1% presented intermediate hyperglycemia, showing the serious problem of the disease in the country (26) . Regarding the other comorbidities that were identified, the findings were similar to those of the study that showed that hypertensive patients had a higher prevalence of dyslipidemia, chronic kidney disease, obesity, diabetes and cardiovascular diseases, including stroke, acute myocardial infarction and angina (27) . The presence of multimorbidities in hypertensive individuals may contribute to potential complications for increased mortality.…”
Section: Discussionsupporting
confidence: 85%
“…Resultados: A prevalência de hipertensão arterial foi de 66,2% e foi a segunda causa básica de óbito (25,6%) identificada na autópsia, precedida de aterosclerose (37,8%). As variáveis associadas à hipertensão foram: gênero feminino (OR = 2,30(1,90); ter um parceiro [OR = 0,55 (0,32-0,92)]; índice de massa corporal [OR = 1,14 (1,08-1,22)] e história de diabetes [OR = 2,39(1,27)]. Conclusão: A prevalência de hipertensão foi elevada e representou a segunda causa básica de óbito mais frequente.…”
unclassified
“…Several population studies have shown that chronic hypertension during midlife (between ages of 35 and 64) increases the risk for developing AD later in life (Launer et al 2000;Feldstein 2012). Midlife hypertension as an independent risk factor may account for up to 8% of all cases of late-onset AD (Barnes and Yaffe 2011) and since hypertension is often comorbid with other risk factors such as obesity and hypercholesterolemia (Noh et al 2016), the cumulative contribution of hypertension to AD is much higher. The mechanism by which midlife hypertension may result in dementia likely stems from the irreversible alterations to the vasculature induced by high blood pressure.…”
Section: Role Of Rocks: Vascular Pathologies and Vascular Risk Factormentioning
confidence: 99%
“…[1][2][3] Furthermore, hypertension and dyslipidemia act synergistically to accelerate CVD progression, 4 and more than one half of patients with hypertension have dyslipidemia. 5,6 Many studies have also shown a positive correlation between blood cholesterol levels and CVD; thus, a reduction in cholesterol levels can significantly reduce the CVD risk. 7 Therefore, the goal of hypertension management is no longer blood pressure (BP) control alone but attenuation of overall CVD risk.…”
Section: Introductionmentioning
confidence: 99%